Enhanced heating mechanism of the electric metal melting furnace in traditional foundry - Mohamed Ariff, Tasnim Firdaus; Zakaria, Zairul Azrul (Asian Research Publishing Network (ARPN), 2015)
The cost to own a furnace to melt metals is very costly; around RM 60, 000 for a 3 litre capacity diesel furnace and may be higher depending upon the crucible capacity. Due to the high cost of raw material i.e. copper and aluminium, the metal industry has become an expensive industry and a burden, especially for the small operators. Thus, this research aims to modify the shape of the heat chamber in the electric furnace in order to improve efficiency and at the same time being affordable to support the traditional foundry. The electric furnace is designed based on the induction concept and used the coil as the heater to melt the non-ferrous metals, namely an aluminium or brass. The conceptual design of the furnace using Solid Works took several important criteria that have been considered; that is the furnace efficiency, the commercial design, the cost involved, the furnace heating mechanism, the heat chamber shape, the internal combustion flow and the mobility of the furnace. The criteria are then analysed by using the Matrix Evaluation Method (MEM) to find the ultimate design that suits the criteria. From the computational simulation, it is found that the heat flow due to the induction accumulates the entire space in the furnace and is capable to melt the metal completely. Results from the repeated experiments show that the melting time for aluminium is only 45 minutes for the quantity of 1 kg at a temperature of 740°C. This design of induction furnace turned out to be reasonably efficient (78.53%) and is very economical (RM 5160). Therefore, this furnace can be a good solution in helping traditional foundries particularly in Malaysia.